Análise teórica de dados espectroscópicos de dihidrochalconas derivadas do produto natural Metrodorea stipularis - NASCIMENTO, Fabiana Cristina de Araújo (2019)
The present work based on the theoretical study saw RMN through the method DFT of the subclass belonging diidrochalconas the class of natural products denominated flavonoides, isolated of the species vegetable Metrodorea stipularis.The Calculations computacionais, have been used thoroughly in aid to the analyses espectroscópicas, as well as in the structural elucidation of organic substances, because given espectrocópicos expe¬rimentais no identified they hinder the acquisition of information on several chemical and structural properties, being the molecular modelling a promising tool for the understanding of those characteristics. The quantum metódo of DFT has if tornado a tool useful computacional to help in the interpretation of experimental data of natural products saw RMN. Recently, they were isolated two dihidrochalconas: 1 - (5,7-dihidroxi-2,2-dimetilcroman-6-il) -3 - (2,2-dimetilcroman-6-il) -3 - [4-hidroxi-3 - (3-metilbut-2-en-1-il-fenil] propan-1-ona and 1 - (5,7-dihidroxi-2,2-dimetilcroman-6-il) -3 - (1,1,4a-trimetil-2,3,4,4a,9a-hexahidro-1H-xantona-7-il) propan-1-ona starting from the species Metrodorea stipularis. The methods computacionais DFT/B3LYP/cc - pvDZ and B3PW91 / DGDZVP were applied for optimization of the studied structures, that when obtained energy mínina were submitted to calculations of chemical (.H and .C) displacements. .H and theoretical .C compared to the experimental ones through Simple Lineal Regression, where it was obtained resulted satisfactory estatisticamente for the correlation (R2) degree and previsibility (Q2) demonstrating, with that, the efficiency of the employed method for the description of the data of RMN of Diidrochalcona 1 and 2. besides, the obtained results allowed to elucidate which the best estereoquímica of Diidrochalcona 2, since that presents two equal of probable enanciômeros.